2013
DOI: 10.3945/ajcn.112.043976
|View full text |Cite
|
Sign up to set email alerts
|

Modulating absorption and postprandial handling of dietary fatty acids by structuring fat in the meal: a randomized crossover clinical trial

Abstract: Background: Prolonged postprandial hypertriglyceridemia is a potential risk factor for cardiovascular diseases. In the context of obesity, this is associated with a chronic imbalance of lipid partitioning oriented toward storage and not toward b-oxidation. Objective: We tested the hypothesis that the physical structure of fat in a meal can modify the absorption, chylomicron transport, and further metabolic handling of dietary fatty acids. Design: Nine normal-weight and 9 obese subjects were fed 40 g milk fat (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 49 publications
3
80
0
5
Order By: Relevance
“…De plus, les activités catalytiques des lipases sont également dépendantes de la présence d'agents tensioactifs. L'efficacité de la lipolyse dépend donc également de la nature de l'interface (Borgström, 1975 ;Reis et al, 2008 ;Vors et al, 2012Vors et al, , 2013. Or, il existe une variété de surfactants qui sont utilisés en IAA et peu de données ont mis en évidence un impact de leur nature vis-à-vis de l'absorption de l'ALA.…”
Section: Biodisponibilité De L'ala Et Effet De L'émulsification Des Lunclassified
“…De plus, les activités catalytiques des lipases sont également dépendantes de la présence d'agents tensioactifs. L'efficacité de la lipolyse dépend donc également de la nature de l'interface (Borgström, 1975 ;Reis et al, 2008 ;Vors et al, 2012Vors et al, , 2013. Or, il existe une variété de surfactants qui sont utilisés en IAA et peu de données ont mis en évidence un impact de leur nature vis-à-vis de l'absorption de l'ALA.…”
Section: Biodisponibilité De L'ala Et Effet De L'émulsification Des Lunclassified
“…Thus, some studies have evidenced the faster absorption and metabolization of emulsified lipids than unemulsified one (Garaiova et al, 2007;Vors et al, 2013). Additionally, the nature of the emulsifiers can affect the metabolism of lymph CM (Daher et al, 2003) and the concentration of TAG in plasma (Keogh et al, 2011).…”
Section: After Absorptionmentioning
confidence: 99%
“…The tendency of a higher triglyceride level postprandial after the LCD with a relatively high content of fat is a result of uptake by the small intestine of fat and the transport of triglycerides of chylomicrons in the blood stream. Prolonged postprandial hypertriglyceridemia is a potential risk factor for cardiovascular disease but the type of fat could be important 85 . However, the importance of postprandial hypertriglyceridemia for the LCD in long term is uncertain in the view of studies that demonstrated lower fasting triglycerides after LCD 30,41,42,86 .…”
Section: Discussionmentioning
confidence: 99%